Analisis Efektivitas Kebijakan Insentif Pajak Penghasilan Final Bagi Pelaku UMKM Pada Masa Pandemi Covid 19 Terhadap Penerimaan Pajak Di KPP Pratama Pondok Aren Tahun 2020 - Camelya Ragil Yulyanti; Khairur Raziqiin (Jurnal Ilmu Administrasi Publik, 2021)
Indonesia had confirmed the Covid-19 outbreak in March 2020. This condition greatly affected economic stability and community productivity as workers and business actors. One of the efforts made by the government in the field of taxation for the recovery of the national economy is by implementing tax incentive policies. One of them is the Final Income Tax relief for MSME actors affected by Covid 19 or the government will bear MSME Income Tax (DTP). The purpose of this study was to analyze the effectiveness of the final income tax incentive policy for MSME actors during the covid 19 pandemic on tax revenues at Pondok Aren Small Tax Office in 2020. The main problem in this study was the level of effectiveness of the tax incentive policy. This study used a qualitative descriptive approach with data collection techniques in the form of interviews, observation, documentation, and triangulation. Based on the results of this study, when viewed from the effectiveness of tax incentives on tax revenues after tax incentives in 2020, it is classified as ineffective with an effectiveness percentage of 58.20%. In this case, the obstacles experienced are socialization or counseling that cannot be done directly (face to face), the lack of information received by taxpayers who are not active in social media and do not understand the contents of this policy. So, in this case, Pondok Aren Small Tax Office must optimize the provision of socialization.